Corporate Structural Changes And Financial Reporting In Nigerian Banking Industry - Fakiyesi, Oyindamola Adesola; Olaoye, Festus (Advances in Social Sciences Research Journal, 2018)
This study examined the impact connection between corporate structural changes and financial reporting in Nigerian Banking Industry. The study specifically analyzed the impact of changes in share capital and change in share premium on profit after tax, and earning per share. The study focused on five commercial banks in Nigerian including Access banks Plc, Diamond banks Plc, First bank Plc, Guaranty trust bank Plc, and First City Monument banks Plc. Secondary data were collected from annual reports of sampled banks over a period of five years (2011-2015) and were analyzed using panel data estimators such as pooled OLS estimator, fixed effect estimator, and random effect estimator. The most consistent and efficient estimator revealed that corporate structural changes measured in terms of changes in share capital has insignificant positive impact of profit after tax given the reported coefficient estimate corresponding to change in share capital that stood at 5.729072 alongside probability value of 0.308. Corporate structural changes measured in terms changes in share premium exert insignificant negative impact on profit after tax given the reported coefficient estimate of -.5492376 alongside probability values of 0.122. Result also showed that corporate structural changes measured in terms of change in share capital exert significant negative impact on earnings per share, while corporate structural changes measured in terms of change in share premium exert insignificant impact on earnings per share. The study established that any changes in the structural composition of finance mix in terms share capital and share premium exert measurable influence of indicators such as profit after tax and earnings per share reported by firms for awareness of the operational outcome for the years to stakeholders including government, regulatory authorities as well as standpoint for investment by prospective investors. Thus firms in the banking industry should objectively design corporate structural framework that can withstand flexibility and dynamics of business operation in the industry, so as to guide against excessive inconsistencies in financial reporting as a result of structural changes.